LYE: a high-performance caching SOAP implementation - Andresen, D.; Sexton, D.; Devaram, K.; Ranganath, V.P. (International Conference on Parallel Processing, 2004. ICPP 2004, 2004)
The Simple Object Access Protocol (SOAP) is a dominant enabling technology in the field of Web services. Web services demand high performance, security and extensibility. SOAP, being based on extensible markup language (XML), inherits not only the advantages of XML, but its relatively poor performance. This makes SOAP a poor choice for many high-performance Web services. We present a new approach to implementing the SOAP protocol using caching on the SOAP server. This approach has significant performance advantages over current approaches while maintaining complete protocol compliance. We demonstrate its practicality by implementing a demonstration system under Linux, giving speedups of over 250% in our sample applications.